Climate suitability as a predictor of conservation translocation failure. Issue 6 (1st July 2020) - Bellis, Joe; Bourke, David; Maschinski, Joyce; Heineman, Katie; Dalrymple, Sarah
Abstract: The continuing decline and loss of biodiversity has caused an increase in the use of interventionist conservation tools, such as translocation. However, many translocation attempts fail to establish viable populations, with poor release site selection often flagged as an inhibitor of success. We used species distribution models (SDMs) to predict the climate suitability of 102 release sites for amphibians, reptiles, and terrestrial insects and compared suitability predictions between successful and failed attempts. We then quantified the importance of climate suitability relative to 5 other variables frequently considered in the literature as important determinants of translocation success: number of release years, number of individuals released, life stage released, origin of the source population, and position of the release site relative to the species' range. Probability of translocation success increased as predicted climate suitability increased and this effect was the strongest among the variables we considered, accounting for 48.3% of the variation in translocation outcome. These findings should encourage greater consideration of climate suitability when selecting release sites for conservation translocations and we advocate the use of SDMs as an effective way to do this. Abstract : Article impact statement : Species distribution models effectively identify climates more likely to lead to successful establishment of translocated populations. Abstract : Idoneidad Climática como Pronosticador del Fracaso de la Reubicación por Conservación Resumen: La continua declinación y pérdida de la biodiversidad ha ocasionado un incremento en el uso de herramientas intervencionistas de conservación como la reubicación. Sin embargo, muchos intentos de reubicación fracasan en el establecimiento de poblaciones viables, y generalmente se identifica a la mala selección de sitios de liberación como el inhibidor del éxito. Usamos modelos de distribución de especies (MDE) para predecir la idoneidad climática de 102 sitios de liberación para anfibios, reptiles e insectos terrestres y comparamos las predicciones de idoneidad entre los intentos fallidos y los exitosos. Después cuantificamos la importancia de la idoneidad climática en relación a otras cinco variables consideradas frecuentemente en la literatura como determinantes importantes del éxito de la reubicación: el número de años de liberaciones, el número de individuos liberados, la etapa de vida durante la liberación, la fuente de la población de origen y la posición del sitio de liberación en relación a la extensión de la especie. La probabilidad del éxito de la reubicación incrementó conforme aumentó la idoneidad climática pronosticada y este efecto fue el más fuerte entre las variables que consideramos, representando el 48.3% de la variación del resultado de la reubicación. Estos hallazgos deberían promover una mayor consideración de la idoneidad climática cuando se seleccionan sitios de liberación para reubicaciones por conservación y abogamos que el uso de los MDE es un método efectivo para hacer esto. 摘要: 生物多样性的持续下降和丧失致使人们更加频繁地使用保护干预措施, 如迁地保护。然而, 许多迁地保护尝试并未能建立可存活的种群, 其中释放位点选择不当往往被认为是阻碍成功的因素之一。我们使用物种分布模型预测了 102 个两栖类、爬行类和陆生昆虫释放位点的气候适宜性, 并比较了成功及失败案例的适宜性预测结果。我们还量化了气候适宜性与其它五个变量相比的相对重要性, 这五个变量经常被相关研究认为是迁地保护成功与否的重要决定因素, 包括: 释放的年数, 释放的个体数目, 被释放动物的生活史阶段, 释放种群的来源, 以及释放位点相对于物种分布范围的位置。我们发现, 迁地成功的概率随着预测气候适宜性的增加而增加, 该效应在本研究考虑的变量中影响最大, 占迁地保护结果变异的 48.3% 。以上结果表明, 应在选择迁地保护释放位点时更多地考虑气候适宜性; 我们建议使用物种分布模型来有效地实现这一目标。【翻译: 胡怡思; 审校: 聂永刚】